Anthrax lethal toxin exerts potent metabolic inhibition of the cardiovascular system - Jie Liu; Zehua Zuo; Rasem Fattah; Toren Finkel; Stephen H. Leppla; Shihui Liu (mBio)
ABSTRACT Bacillus anthracis causes anthrax through a combination of bacterial infection and toxemia. As a major virulence factor of B. anthracis, anthrax lethal toxin (LT) is a zinc-dependent metalloproteinase, exerting its cytotoxicity through proteolytic cleavage of the mitogen-activated protein kinase kinases, thereby shutting down the MAPK pathways. Anthrax lethal toxin induces host lethality mostly by targeting the cardiovascular system. Although the enzymatic activity and the molecular targets of LT have long been known, the detailed mechanisms underlying cellular/tissue/organ toxicity are still poorly understood. In this work, we sought to investigate the mechanism of LT-induced cellular damage in the cardiovascular system. We demonstrate for the first time that anthrax lethal toxin has potent inhibitory effects on the central metabolism of cardiomyocytes and endothelial cells. This is likely due to the observed downregulating of c-Myc expression through the toxin-induced inhibition of the ERK pathway. Since c-Myc is a master transcription factor controlling the expression of many rate-limiting metabolic enzymes in glycolysis and the tricarboxylic acid cycle, LT’s downregulation of c-Myc may lead to the observed bioenergetic collapse, particularly, in cardiomyocytes. Since cardiac cell contraction requires continuous production of large amounts of ATP, potent inhibition of the bioenergetics of cardiomyocytes would be incompatible with life. Thus, LT-induced lethality through targeting cardiomyocytes and endothelial cells appears to be a consequence of a bioenergetic collapse, likely due to the toxin’s potent inhibitory activity on the MEK-ERK-c-Myc-metabolic/bioenergetic axis within these target cells of cardiovascular system.IMPORTANCEAnthrax lethal toxin (LT) is a major virulence factor of Bacillus anthracis, the causative pathogen of anthrax disease. Anthrax lethal toxin is a metalloproteinase that cleaves and inactivates MEKs, thereby shutting down MAPK pathways, leading to host mortality primarily through targeting of the cardiovascular system. However, the detailed mechanisms underlying the toxin’s cellular and tissue toxicity are still poorly understood. Here, we found that anthrax lethal toxin has potent inhibitory activity on glycolysis and oxidative phosphorylation of cardiomyocytes and endothelial cells. These effects appear to be the consequence of downregulation of c-Myc, a master transcription factor that controls many rate-limiting enzymes of glycolysis and the tricarboxylic acid cycle. With the high demand on energy for cardiac contraction, the potent inhibition of cardiomyocyte metabolism by LT would be incompatible with life. This work provides critical insights into why the cardiovascular system is the major in vivo target of LT-induced lethality.